Recent Advances in Host‐Guest Supramolecular Hydrogels for Biomedical Applications. Issue 18 (5th August 2022) - Wang, Suxi; Ong, Pin Jin; Liu, Songlin; Thitsartarn, Warintorn; Tan, Maureen Janet Beng Hoon; Suwardi, Ady; Zhu, Qiang; Loh, Xian Jun
Abstract: The recognition‐directed host‐guest interaction is recognized as a valuable tool for creating supramolecular polymers. Functional hydrogels constructed through the dynamic and reversible host‐guest complexation are endowed with a great many appealing features, such as superior self‐healing, injectability, flexibility, stimuli‐responsiveness and biocompatibility, which are crucial for biological and medicinal applications. With numerous topological structures and host‐guest combinations established previously, recent breakthroughs in this area mostly focus on further improvement and fine‐tuning of various properties for practical utilizations. The current contribution provides a comprehensive overview of the latest developments in host‐guest supramolecular hydrogels, with a particular emphasis on the innovative molecular‐level design strategies and hydrogel formation methodologies targeting at a wide range of active biomedical domains, including drug delivery, 3D printing, wound healing, tissue engineering, artificial actuators, biosensors, etc. Furthermore, a brief conclusion and discussion on the steps forward to bring these smart hydrogels to clinical practice is also presented. Abstract : Host‐guest supramolecular hydrogels exhibit superior self‐healing, injectability and stimuli‐responsiveness, due to the dynamic and reversible interactions. This paper provides an overview of the state‐of‐art developments in these smart soft materials for a wide range of biomedical applications, highlighting the innovative design strategies at molecular‐level for achieving well‐developed characteristics for specific purposes.